Religious moderation as pedagogical habitus in Islamic religious education: A case study of internalization and character formation - Imam Hanafie; Khojir Khojir; Shafa Shafa; Taufikin Taufikin; Mohammad Taqi Fakhlaei (Bulletin of Educational Management and Innovation, 2026)
Background: Religious moderation has become a strategic issue in education amid rising signs of intolerance and radicalism among adolescents, particularly at the secondary school level, which is a crucial phase in identity formation. Although the value of moderation has been integrated into the Islamic Religious Education curriculum, its implementation remains largely normative and has not yet fostered a deep internalization process within learning practices. Purpose: This study aims to analyse how the values of religious moderation are constructed and internalized in Islamic Religious Education learning and how they contribute to the formation of students’ attitudes. Method: This study employs a qualitative approach with a case study design, conducted at a high school in Indonesia. Data were collected through observation, in-depth interviews, and document analysis, and were analysed using inductive thematic analysis. Findings: The results indicate that religious moderation is not merely taught as a value but is formed as a pedagogical habitus through the interaction between the curriculum structure, teacher role modelling, and repeated social practices. The internalization process occurs through the mechanisms of role modelling, reflective dialogue, and habituation, resulting in social empathy, self-control, and harmony in diversity. These findings offer a new conceptual contribution by positioning religious moderation as a pedagogical habitus in education.